1002 Improving the Medical Student Experience of Trauma and Orthopaedic Education – a Quality Improvement Project. (19th August 2022) - Khanom, S; Nebo, V; Noton, T; Garlick, Ni; Maruthainar, N
Abstract: Aim: The medical student experience of clinical placements is closely linked with quality of teaching, varied educational opportunities and sense of belonging within the team. Surgical rotations such as Trauma and Orthopaedics (T&O) have a stereotype for being challenging. At a London teaching hospital student satisfaction of T&O placements was low (8% satisfaction) as assessed by feedback. This quality improvement (QI) project aimed to improve the quality of educational experiences and overall student satisfaction in T&O. Method: Student feedback from end of placement evaluation forms from academic years 2016–19 was reviewed. A QI driver diagram was created based on the themes raised in the feedback. These were 1) formal teaching, 2) structure and organisation, 3) curriculum content and 4) student engagement and belonging. Each theme was subdivided into multiple achievable strategies to improve student experience while on T&O placements. This included allocated clinic and theatre sessions, bedside teaching, named tutors, curriculum map, WhatsApp communication and a dedicated clinical teaching fellow in the department. Results: As a result of the implemented QI strategies, student satisfaction improved over the subsequent semesters to 100%, 89%, 100% and 75%, with a greater number of students providing feedback. Conclusions: The project achieved greater student satisfaction of T&O education and improved the student experience of surgical placements. It also validates student feedback as a valuable tool in developing surgical education.